Corrosion Study of Galvanized Ultra High Strength Steel Reinforced Overhead Transmission Conductors - Azam Khan, Amir; Bong Boon Liang, David; Ragai Henry Rigit, Andrew; Soh Fong, Lim; Othman, Al-Khalid; ., . (International Journal of Engineering and Technology, 2018)
Overhead high voltage transmission conductors used worldwide are produced in several configurations. A multi-strand conductor of the type ACSR330 is typically used for 275 kV overhead transmission lines. The conductor is composed of 7 inner strands of Ultra High Strength Galvanized Steel for the mechanical support of the conductor and 26 strands of high conductivity Aluminum wires meant for power transfer over long distances. During the use, weather conditions and power fluctuations tend to degrade the properties of these conductors. In the present work, study of the state of galvanization and oxidation of an ACSR330 conductor is undertaken with a view to understand the effectiveness of the loss in corrosion protection and changes in the zinc coating on the galvanized steel strands after use for 25 to 30 years. The Scanning Electron Microscopy (SEM), X Ray Diffraction (XRD) and Energy Dispersive Analysis through X rays (EDAX) provide a very useful insight into the state of the conductor and gives important information to the strategic decision maker, whether or not to replace the conductor. It was observed in the present study that the zinc coating diffuses inside the steel strand under temperature and time effect. This unique study on the used conductors also reveals that the morphology of the coating and its interface structure changes significantly compared to an unused conductor of the same age.Â Â Â Â